2019
DOI: 10.1038/s41560-019-0430-2
|View full text |Cite
|
Sign up to set email alerts
|

Life-cycle energy and climate benefits of energy recovery from wastes and biomass residues in the United States

Abstract: A t the beginning of the new millennium, energy insecurity, global climate change and stagnant rural economies led to policies supporting domestic biofuels as a renewable alternative fuel in more than 60 countries worldwide 1. As a consequence, global production of ethanol and biodiesel combined almost quadrupled (from about 35 billion litres to 135 billion litres) in the short span from 2005 to 2016 (ref. 2). However, these policies had two major flaws. First, appropriation of edible crops for biofuel (mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(50 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…Although the conversion technology and energy conversion coefficients would change heavily in the future, some assumptions are made based on the conversion technology trends and the actual utilization at present as follows: (a) electricity and heat, biogas, and bioethanol are three kinds of final bioenergy in this research. (b) According to the public preferences and climate benefit research of energy recovery from wastes and biomass residues (Liu & Rajagopal, ; Zhao, Cai, Li, & Ma, ), thermal combustion through biomass‐assisted heat and power plants is the optimal pathway for woodland and agricultural residues, and thermal combustion is therefore adopted for all the residues in this research. (c) According to the actual utilization of waste at present (National Bureau of Statistics, ; ), all the municipal sewage sludge and animal manure are used for biogas production via anaerobic digestion while considering the process of cleaning and compression, half of the municipal waste is converted into biogas via anaerobic digestion, and the rest of the municipal waste is used for thermal combustion.…”
Section: Methodsmentioning
confidence: 99%
“…Although the conversion technology and energy conversion coefficients would change heavily in the future, some assumptions are made based on the conversion technology trends and the actual utilization at present as follows: (a) electricity and heat, biogas, and bioethanol are three kinds of final bioenergy in this research. (b) According to the public preferences and climate benefit research of energy recovery from wastes and biomass residues (Liu & Rajagopal, ; Zhao, Cai, Li, & Ma, ), thermal combustion through biomass‐assisted heat and power plants is the optimal pathway for woodland and agricultural residues, and thermal combustion is therefore adopted for all the residues in this research. (c) According to the actual utilization of waste at present (National Bureau of Statistics, ; ), all the municipal sewage sludge and animal manure are used for biogas production via anaerobic digestion while considering the process of cleaning and compression, half of the municipal waste is converted into biogas via anaerobic digestion, and the rest of the municipal waste is used for thermal combustion.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, when other supply chains are created, competition between traditional industries is avoided, such as pulp and paper or the production of wood pellets, with the production of energy [49][50][51]. This non-competition allows, first, the use of resources that until now have not been used, and therefore, with low market value, its cost depending only on the complexity of its supply chain; and, second, the creation of a truly sustainable option, in a perspective of circular economy, where all resources are valued, to the detriment of the intensive exploitation of forest resources [52][53][54].…”
Section: State-of-the-artmentioning
confidence: 99%
“…Liu and Rajagopal (2019) use life‐cycle assessment to evaluate the potential of agricultural and forestry residues, municipal solid waste, and animal manure to generate renewable energy within the United States. They found that the utilization of these available wastes and residues could deliver 2.4–3.2 EJ of net energy gain and displace 103–178 million tons of CO 2 ‐equivalent of greenhouse gas emissions.…”
Section: Biofuel Residuesmentioning
confidence: 99%